The relationship of the plant protection and the applied technology in the integrated apple production - Csihon, Á.; Holb, I. J.; Gonda, I. (International Journal of Horticultural Science, 2013)
The indirect elements of the integrated plant protection can infl uence the effectiveness of the chemical control, however their significance are often extenuated. The characteristic of the plants are almost completely disregarded at the protection decisions. The condition can determinate basically the rate of the damages caused by the pests. The plant in good conditional state has higher tolerance and lower susceptibility against the pests. With the optimal general and annual condition we can establish and maintain the harmony between the growth and the bearing, what is the basis of effective plant protection.